Developing Civic Literacy-Based Explosion Box to Enhance Pancasila Education Learning Outcomes - Muthia Resty; Reh Bungana Beru Perangin-angin; Yusnadi; Hapni Laila Siregar; Restu; Zuraida LBS (Researchparks Publishing, 2026)
Pancasila education is a crucial subject within the Merdeka Curriculum that requires creativity in delivering instructional materials to strengthen the civic literacy of primary school students. This study serves as a development research project for an innovative instructional medium specifically designed to support the active learning process for fifth-grade students at SD Negeri 132410 Tanjungbalai. The study aims to produce a civic literacy-based Explosion Box learning medium on the topic of